2019
DOI: 10.22462/01.03.2019.4
|View full text |Cite
|
Sign up to set email alerts
|

Modification of HIF-1α, NF-κB, IGFBP-3, VEGF and adiponectin in diabetic foot ulcers treated with hyperbaric oxygen

Abstract: Introduction: Diabetic foot ulcers are a frequent complication of diabetes and the first cause of non-traumatic lower limb amputation. They affect quality of life, restrict social productivity and generate a high economic burden for health care systems. Hyperbaric oxygen (HBO2) therapy is an adjunctive treatment option because it improves wound healing in the short term. However, its ability to modulate the pro- and anti-inflammatory balance and the hypoxic cell response in the clinical setting has not been fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Furthermore, a combination of HBOT and either chemotherapy or radiotherapy may provide better treatment in cancer therapy. In addition to p53 protein, HBOT could decrease the HIF-1α protein in A549 and Beas-2 cells, which supported the hypothesis that HBOT could ameliorate the hypoxic condition in cancer cells 42 , 43 . Combined with our in vivo and in vitro findings suggest that tumor microenvironment interacting with tumor cells is significantly impacted after HBOT in lung cancer.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, a combination of HBOT and either chemotherapy or radiotherapy may provide better treatment in cancer therapy. In addition to p53 protein, HBOT could decrease the HIF-1α protein in A549 and Beas-2 cells, which supported the hypothesis that HBOT could ameliorate the hypoxic condition in cancer cells 42 , 43 . Combined with our in vivo and in vitro findings suggest that tumor microenvironment interacting with tumor cells is significantly impacted after HBOT in lung cancer.…”
Section: Discussionsupporting
confidence: 70%
“…Growth factors and other angiogenesis-promoting cytokines induce new vessel formation by increased expression of pro-angiogenesis genes, which is mediated by NF-κB or (under hypoxia) HIF-1α [162,163]. Since the current review demonstrates an inhibiting effect of HBOT on both transcription factors and little research, with contradicting outcomes, into the downstream effectors of angiogenesis (i.e., PI3K, Akt, p38 MAPK, ERK) has been done, it is unclear how increased levels of pro-angiogenesis growth factors and cytokines actually induce increased tube formation, as shown by Anguiano-Hernandez et al [125], Lin et al [130] and Shyu et al [40]. Thus, further research into the relation between NF-κB, HBOT and the angiogenesis pathways is needed.…”
Section: Discussionmentioning
confidence: 80%
“…According to Niu et al [52,72], the effect on MMPs is delayed and only manifests after two or three HBOT sessions. Hypoxia-inducible factor-1α (HIF-1α) and NF-κB were inhibited by HBOT (see Tables 2 and 3), although Anguinano-Hernandez et al [125] described an increase in NF-κB in the cytosol.…”
Section: Angiogenesismentioning
confidence: 99%
“…While a recent study in rabbits treated with HBOT found no significant changes to the expression of genes involved in wound healing [ 146 ], a study using a diabetic mouse model found accelerated wound healing and a significant reduction in MMP-9 levels with treatment [ 147 ]. In a small study with 17 patients, hyperbaric oxygen therapy was noted to induce cytoplasmic translocation of HIF-1a and nuclear factor (NF)-kB localization as well as increased VEGF, IL-6, insulin-like growth factor binding protein 3, adiponectin, fibrosis, and angiogenesis while decreasing interferon (IFN)-γ levels [ 148 ]. In addition, the prolonged use of hyperbaric oxygen therapy has also been shown to decrease the recruitment and adhesion of neutrophils, increase oxygen dispersion to damaged tissues, reduce inflammation, and accelerate healing in patients with diabetic ulcers [ 149 , 150 , 151 ].…”
Section: Treatment Strategiesmentioning
confidence: 99%